Diversified responses of vegetation carbon uptake to urbanization: a national-scale analysis - Zhang, Xueliang; Qiu, Dai; Xie, Yichun; Tu, Jianguang; Lan, Hai; Li, Xiaolei; Sha, Zongyao (Frontiers in Ecology and Evolution, 2023)
Introduction Urbanization converts vegetated lands into impervious surfaces and often degrades vegetation carbon sequestration in urban ecosystems. At the same time, the impact on urban vegetation growth from urban expansion could be spatially diverse given different natural environments and urban management practices. Methods Here we applied time-series remotely sensed images and analyzed the urban growth for all the prefecture-level cities across China during 2001–2019, and compared the impact of urbanization on vegetation carbon uptake proxied by MODIS (MOD17A2H) net primary productivity (NPP) on Google Earth Engine platform. Results The result indicated that at the national scale, the carbon uptake flux in urban areas was only 19% compared to that in the nonurban vegetated counterparts. The total urban area expanded by 22% and the vegetation carbon uptake in the newly urbanized zones was averagely reduced by 16% during the period, but with high spatio-temporal heterogeneity among cities and with exceptions demonstrating even improved NPP, highlighting diversified responses of vegetation carbon sequestration to urban sprawl. The changes of vegetation carbon sequestration in response to urbanization were found to be spatially clustered. Discussion We conclude that urban land management strategies unique to cities may attribute to the diversified responses of vegetation carbon capture to urbanization.